Urban resilience through diversity - Nduku, Ntsindiso (School of Architecture, Planning and Geomatics, 2025)
The objective of the research is to contribute to the development of the theory and body of knowledge that seeks to address urban sprawl, spatial inequalities, and spatial fragmentation left by the legacy of apartheid planning. I begin my research with the investigation of existing levels of Diversity, and I employ mapping to see the area which reflects more di¬verse characteristics. Furthermore, I seek to develop a design framework that links the social, economic, and environment. The objective of the framework is to inform the acknowledgement of existing Diversity, the making of sensitive interventions that will improve existing Diversity, and the addition of more diverse elements which will enhance the urban performance of Gugulethu. Kayatekin, 2019 argues that urban Diversity contributes towards resilient and sustainable cities. He argues that for one to understand the importance of Diversity in an urban context, there needs to be an understanding of the meaning and definition of Resilience. According to Kayatekin, 2019, Landman 2012, there are differ¬ent meanings of Resilience in urban terms. Kayatekin, 2019 also simplifies the definition into two parts, with one drawing from Material Science and another from Ecology. The fundamental tenet of this argument is the placing of urban Diversity as the cornerstone for cities' Resilience. I likened this perspective to that of Zuniga-Teran's, 2016, point of view, which describes Diversity as a critical element of urban Resilience